2003
DOI: 10.1007/s00426-002-0093-6
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the distance of an external focus of attention enhances learning

Abstract: Previous studies (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
263
9
21

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(318 citation statements)
references
References 13 publications
25
263
9
21
Order By: Relevance
“…The advantage of the EF strategy is explained by the constrained-action hypothesis; attempts to consciously monitor/control body movements (IF strategy) interfere with automatic motor control processes. However, the interference can be weakened by applying the EF strategy6. This hypothesis is also supported by empirical findings based on movement correction frequency6, attentional-capacity demands7, and electromyography during motor learning tasks8.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…The advantage of the EF strategy is explained by the constrained-action hypothesis; attempts to consciously monitor/control body movements (IF strategy) interfere with automatic motor control processes. However, the interference can be weakened by applying the EF strategy6. This hypothesis is also supported by empirical findings based on movement correction frequency6, attentional-capacity demands7, and electromyography during motor learning tasks8.…”
supporting
confidence: 59%
“…Externally focused attention has been considered the more effective strategy for motor control tasks based on the constrained-action hypothesis, which presumes that conscious monitoring and control of body movement (IF strategy) interferes with automatic motor control processes whereas this interference can be weakened by the EF strategy6. Further, predictive eye movements towards the goal during goal-directed motor tasks28 would support EF as the spontaneous (natural) attentional strategy.…”
Section: Discussionmentioning
confidence: 99%
“…There is a considerable body of evidence to suggest that adopting differential attentional foci results in performance differences at retention (Wulf et al, 1999, 2002; McNevin et al, 2003). However, results of the current investigation revealed no performance differences following acquisition trials.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, researchers have distinguished between distal and proximal external foci. For example, McNevin et al (2003) used a stabilometer balance task and demonstrated that a distal external focus of attention on balancing platform markers placed 26 cm away from participants’ feet resulted in enhanced learning compared to a proximal external focus that required participants to focus on markers placed immediately in front of their feet, which, in turn, was more effective than an internal focus of attention. It appears that an external focus has more beneficial effects on learning when the direction of focus is remote from the action effects that produce the movement.…”
Section: Introductionmentioning
confidence: 99%